The Effect of Telenursing-Based Health Education on Self-Efficacy in Tuberculosis in Hospital Setting Patients - Achmad Wahdi; Ah Yusuf; Eppy Setiyowati; Dewi Retno Puspitosari; Erik Irham Lutfi (Institut Kesehatan YARSI Mataram, 2025)
Pulmonary TB treatment, which takes a relatively long time with regular medication intake, causes patient boredom with the treatment. The informational and emotional support provided is also less than optimal; this can reduce self-efficacy. This research aims to determine the effect of telenursing-based health education on self-efficacy in tuberculosis patients at the Jemursari Islamic Hospital, Surabaya. This was a quasi-experimental pre-post test control group design approach. Population of 38 tuberculosis patients at Jemursari Islamic Hospital, Surabaya. The sample size was 38 patients, divided into 2 intervention and control groups, taken using random sampling techniques based on sample allocation. Data was collected using a questionnaire. Data analysis used the Paired t-test and Independent t-test with α = 0.05. The research results showed that the difference between the self-efficacy of the intervention group was X ± (SD) = 7.05 ± (4.47) and the control group, namely X ± (SD) 0.11 ± (0.315). The results of the Independent t-test¸ ρ = 0.000, meaning that there is an influence of telenursing-based health education on increasing self-efficacy in tuberculosis patients. Telenursing-based health education can increase self-efficacy. Hospitals and nurses can use telenursing (long distance care) to provide health education to patients with chronic diseases such as tuberculosis ABSTRAK Pengobatan TB Paru yang memakan waktu relatif lama dengan asupan obat yang teratur menyebabkan pasien bosan terhadap pengobatan, kemudian dukungan informasional dan emosional yang diberikan juga kurang optimal, hal ini dapat menurunkan efikasi diri. Penelitian ini bertujuan untuk mengetahui pengaruh pendidikan kesehatan berbasis telenursing terhadap efikasi diri pada pasien tuberkulosis di Rumah Sakit Islam Jemursari Surabaya. Desain penelitian ini adalah quasi experimental dengan pendekatan pre post test control group design. Populasi 38 pasien tuberkulosis di Rumah Sakit Islam Jemursari Surabaya. Besar sampel sebanyak 38 pasien, dibagi menjadi 2 kelompok intervensi dan kontrol, diambil dengan menggunakan teknik random sampling berdasarkan alokasi sampel. Data dikumpulkan dengan menggunakan kuesioner. Analisis data menggunakan uji Paired t-test dan Independent t-test dengan α = 0,05. Hasil penelitian menunjukkan selisih efikasi diri kelompok intervensi yaitu X ± (SD) = 7,05 ± (4,47) dengan kelompok kontrol yaitu X ± (SD) 0,11 ± (0,315). Hasil uji t-independent ρ = 0,000, artinya ada pengaruh edukasi kesehatan berbasis telenursing terhadap peningkatan efikasi diri pada pasien tuberkulosis. Edukasi kesehatan berbasis telenursing dapat meningkatkan efikasi diri. Rumah sakit dan perawat dapat memanfaatkan telenursing (long distance care) untuk memberikan edukasi kesehatan pada pasien dengan penyakit kronis seperti tuberkulosis.